A year of public laparoscopic sleeve gastrectomy - Gabsi, Kheira; Siow, Yian Y.; Hariswamy, Soumya; Garcia, Naydeli; Zarrouk, Ali (International Surgery Journal, 2024)
Bariatric surgery is becoming increasingly prominent in Australia, however over 90% is still performed in the private sector. We examined the outcomes of the first year of our publicly funded bariatric surgery program, which includes regular review in a metabolic clinic by an Endocrinologist and Allied Health. The characteristics and outcomes of 22 consecutive patients who underwent publicly funded Laparoscopic Sleeve Gastrectomy with a single surgeon at a South-West Sydney public hospital between March 2023 and May 2024 were retrospectively collected. Data on patient characteristics, operative details and post-operative outcomes was collected and analysed. The majority of patients were women (77%), with a mean age of 48±10.6. Mean initial weight at program commencement was 136.7±25.7 kg, and mean BMI 49±6 kg/m2. All patients had >2 obesity related comorbidities; 45% were diabetic. There were no complications or re-admissions. At 6 months post-op, mean weight loss from baseline weight was 34.3±17 kg, with mean TBWL 24.8% ± 9.6% and EBWL 52%±17.7%. For patients with 12 month follow up data, mean weight loss was 46.6 kg±27.9, with mean TBWL of 33%±14% and EBWL of 68 %±23%. Our first year of public Laparoscopic Sleeve Gastrectomy, in conjunction with a comprehensive metabolic program, has been shown to be safe and effective, with preliminary data demonstrating outcomes equivalent to those previously published.